Managing Human Resource in the Digital Economy: Balancing Challenges and Opportunities - Suwaji, Rifki; Hepiyanto; Rina Indra Sabella; Waloyo; Rohmah Kurniawati (SEULANGA SYSTEM PUBLISHER, 2024)
Digital technologies enable the adoption of more efficient working models, such as process automation, predictive analytics for better decision making, and the use of digital platforms for employee development and performance management. This study aims to investigate employee perceptions and experiences of digital transformation in the context of challenges and opportunities at the company PT Charoen Pokphand Indonesia (CP) Food. The research method used is descriptive qualitative with a data collection approach through questionnaires and observations. The questionnaire was designed to collect employee responses on various aspects of digital transformation in terms of opportunities and challenges. Using a purposive sampling approach, which is a sampling method in which the researcher deliberately selects certain participants or sample units based on certain characteristics or criteria that are considered relevant to the research objectives. The results showed that employees have a positive view of digital transformation at the company PT Charoen Pokphand Indonesia (CP) Food. Employees see it as an opportunity for career development and professional growth, and feel supported in developing their digital skills. A work culture that supports collaboration, innovation, and creativity is also considered important in creating a productive and dynamic work environment. The integration of digital technology is considered successful by employees, indicating that the company has successfully implemented technology in daily work processes well. This research provides valuable insights into how digital transformation affects employee perceptions and experiences in the work environment. The implications of these findings can be used by companies to design more effective human resource management strategies to face the challenges and opportunities in the evolving digital economy.